Cerebrospinal fluid cytological and biochemical characteristics in the presence of CNS neoplasia Características citológicas e bioquímicas do líquido cefalorraquidiano na presença de neoplasias no SNC - Sérgio M. de Almeida; Edna Nanakanishi; Arnaldo J. de Conto; Luciana P. Souza; Dario Antonelli Filho; Carlos D. Roda (Arquivos de Neuro-Psiquiatria)
Central nervous system (CNS) infiltration must be ruled out in patients with known neoplastic diseases and neurological symptoms. It was done a retrospective analysis of 1,948 CSF samples from patients with suspected malignant infiltration in the CNS, in order to evaluate the positivity rate of malignant cells in cerebrospinal fluid (CSF) samples and correlate with cytochemical characteristics. Sixty-two percent of subjects had acute lymphocytic leukemia. Malignant cells were found in 24% of all CSF samples. Subjects with positive malignant cells had predominance of increased levels of CSF total protein (TP), glucose and total cytology (p<0.05). Mean total cell count in this group was 232 (SD 933) cells/mm³, compared to 9 (SD 93) cells/mm³ in the group without neoplasic cells (p=0.029). CSF TP specificity was 87% and negative predictive value (NPV) 96%. CSF total cell count specificity 86% and NPV 97%. Although sensitivity and positive predictive value were low. The presence of inflammatory cells and elevated TP found in patients with malignant cells in the CSF can aid in diagnosing CNS neoplasms. A infiltração neoplásica no SNC deve ser afastada em pacientes com neoplasia e sintomas neurológicos. Foi realizada uma análise retrospectiva de 1.948 amostras de LCR de pacientes com suspeita de infiltração neoplásica no SNC. Sessenta e dois por cento dos pacientes eram portadores de leucemia linfocitica aguda. Células neoplásicas foram encontradas em 24% de todas as amostras. Houve níveis aumentados no LCR da proteína total (PT), glicose e de citologia global (p<0.05), no grupo com presença de células neoplásicas. A média da contagem global de células no LCR, neste grupo, foi 232±933 cels/mm³, contra 9±93 cells/mm³ no grupo sem células neoplásicas no LCR (p=0,029). O aumento de PT no LCR apresentou especificidade 87% e valor preditivo negativo (VPN) 96%. A contagem global de células no LCR apresentou especificidade 86% e VPN 97%. Porém sensibilidade e valores preditivos positivos foram baixos. A presença de células inflamatórias e PT no LCR elevada em pacientes com neoplasias pode ser um indicador do envolvimento no SNC.